From surviving to thriving: A catalyst for MSME creativity - Sugiono, Edi; Pallawagau, Andi; Sutikman, Sutikman; Hardini, Resti; Kusumaningrum, Anisa Putri; Sari, Santi Retno (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
This study delves into the vital role of creativity in empowering Micro, Small, and Medium Enterprises (MSMEs) to survive and flourish in an increasingly competitive market landscape. The authors present a comprehensive framework designed to cultivate creativity and innovation within MSMEs, which includes key components such as fostering an entrepreneurial mindset, building robust networks, and ensuring access to essential resources. By implementing this framework, MSMEs can effectively navigate the challenges posed by limited resources and rapidly evolving market conditions. The research underscores the significance of creativity as a driving force behind MSMEs' growth and competitiveness, illustrating how innovative approaches can lead to enhanced performance and sustainability. Furthermore, the study offers valuable insights for a diverse audience, including entrepreneurs seeking to enhance their business strategies, policymakers aiming to create supportive environments for MSMEs, and academics interested in the dynamics of small business development. Ultimately, this research contributes to a deeper understanding of how fostering creativity can catalyze the advancement of MSMEs in Indonesia, promoting economic resilience and innovation in the region. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.